SORLA regulates calpain‐dependent degradation of synapsin. Issue 9 (25th March 2016) - Hartl, Daniela; Nebrich, Grit; Klein, Oliver; Stephanowitz, Heike; Krause, Eberhard; Rohe, Michael
Abstract: Introduction: Sorting‐related receptor with A‐type repeats (SORLA) is an intracellular sorting receptor in neurons and a major risk factor for Alzheimer disease. Methods: Here, we performed global proteome analyses in the brain of SORLA‐deficient mice followed by biochemical and histopathologic studies to identify novel neuronal pathways affected by receptor dysfunction. Results: We demonstrate that the lack of SORLA results in accumulation of phosphorylated synapsins in cortex and hippocampus. We propose an underlying molecular mechanism by demonstrating that SORLA interacts with phosphorylated synapsins through 14‐3‐3 adaptor proteins to deliver synapsins to calpain‐mediated proteolytic degradation. Discussion: Our results suggest a novel function for SORLA which is in control of synapsin degradation, potentially impacting on synaptic vesicle endocytosis and/or exocytosis.